MINI-SYMPOSIUM ON FOOD VULNERABILITY IN SOCIETY: Sentinal Chemical Messengers:Endocannabinoid signaling transcends pain - Stefano, George B.; Kream, Richard M. (Archives of Medical Science, 2009)
On a comparative level D9-tetrahydrocannabinol has been shown to have actions in diverse organisms that extend into invertebrate phyla. Furthermore, these same animals have been found to contain endogenous cannabinoid-like molecules with correspondingly high affinity and selective receptors for these chemical messengers. Interestingly, cannabinoid receptors when activated by their respective ligand appear to be coupled to constitutive nitric oxide release in diverse tissues. Cannabinoid actions include modulatory roles in immune, vascular, neural and other tissues, demonstrating that their influence is widespread in different physiological systems. The fact that similar signaling with the same molecules, receptors and nitric oxide release also occurs in invertebrates speaks to the origin of cannabinoid processes. In this regard, these chemical messengers are similar to others such as opioid, opiate, monoaminergic, cholinergic and GABAnergic, etc., which also are identical to that found in mammals. Thus, it would appear that both intra- and inter-cellular communication evolved early to meet the communication requirement necessary for the required high number of integrative processes that would continue to evolve. Simultaneously, cannabinoid signaling may counter-intuitively serve as a sentinel, providing a health glimpse of the animal exhibiting its signaling given the number of functions it is involved with. In this regard, it may also have medicinal properties.